2004
DOI: 10.1111/j.1524-4725.2004.30501.x
|View full text |Cite
|
Sign up to set email alerts
|

Lower Adverse Event and Mortality Rates in Physician Offices Compared with Ambulatory Surgery Centers: A Reappraisal of Florida Adverse Event Data

Abstract: Florida's adverse event data do not show higher adverse event rates in physician offices compared with ambulatory surgical centers. Incident reporting and public availability of incidents are important, as is standardization of reporting rules for both adverse events and number of procedures performed in different settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…The first is that there were no deaths in this study due to officebased surgery performed by dermatologists, and therefore one would conclude on the basis of this study that dermatologic surgery by a dermatologist in an office is indeed safe. The second is that 7 comparing the adverse event and mortality rates of procedures performed in physician offices and ambulatory surgical centers. Based on National Ambulatory Medical Care Survey data, the adverse effect rate and mortality rates were 2.1 and 0.41 per 100,000 procedures, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The first is that there were no deaths in this study due to officebased surgery performed by dermatologists, and therefore one would conclude on the basis of this study that dermatologic surgery by a dermatologist in an office is indeed safe. The second is that 7 comparing the adverse event and mortality rates of procedures performed in physician offices and ambulatory surgical centers. Based on National Ambulatory Medical Care Survey data, the adverse effect rate and mortality rates were 2.1 and 0.41 per 100,000 procedures, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the significant growth in the number of ambulatory surgical procedures provided in the U.S. and associated overall costs [4], researchers have begun to examine differences in quality outcomes for procedures performed in freestanding ambulatory surgical centers (ASCs) and hospital-based outpatient departments (HOPDs) [5][6][7][8][9][10][11][12][13][14][15]. Overall, these studies have utilized varying risk-adjustment approaches and have generally produced mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a comparison of office-based and ambulatory surgery centerebased procedures revealed lower adverse event and mortality rates with office-based surgery. 12 Regulations requiring these elements may therefore not result in increased safety as intended.…”
Section: Safety In An Office-based Setting Key Pointsmentioning
confidence: 98%
“…Some of the most useful data revealing complications during office-based procedures have been compiled from a mandatory reporting database for office procedures in Florida. [11][12][13][14] Initial prospective analysis of the first year in that database revealed that most serious complications resulted from office-based liposuction when performed under general anesthesia. 14 At 7 years, 174 incidents were reported, including 31 deaths.…”
Section: Safety In An Office-based Setting Key Pointsmentioning
confidence: 99%